PENERAPAN BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA PADA PT. HASJRAT ABADI CABANG DIPONEGORO PALU - Evan, Ariel; Sondakh, Jullie J.; Pusung, Rudy J. (Universitas Sam Ratulangi, 2021)
PT. Hasjrat Abadi Diponegoro Palu Branch, has business activities that focus on selling Toyota four-wheeled vehicles and spare parts related to Toyota. This study aims to determine the performance of PT. Hasjrat Abadi Diponegoro Palu Branch by looking at every perspective on the Balanced Scorecard, such as financial perspective, customer perspective, internal business process perspective and learning and growth perspective. The data analysis method used is descriptive qualitative method. The results showed that the financial perspective has increased year by year. The customer perspective shows the company is able to acquire and retain customers, and handle incoming complaints. From the perspective of internal business processes, the company has already performed after-sales services to meet customer needs. From the perspective of learning and growth, the company has not been able to retain its employees, lack of employee training but employee performance is good because there is an increase in employee productivity each year.